High-filling low-heterogeneity composite material with introduced vitrimer micro-crosslinking structure as well as preparation method and application of high-filling low-heterogeneity composite material

The introduction of a vitrimer micro-crosslinked structure and solid-phase shear milling in polymer composites addresses the heterogeneity challenge, improving mechanical and functional performance in high-filler-content materials.

CN120310177APending Publication Date: 2025-07-15SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510383439.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

While meeting the functional requirements, existing high-filled polymer composites are difficult to take into account high mechanical properties, and conventional modification methods have little effect, which cannot effectively weaken the heterogeneity between the inorganic filler and the polymer matrix.

Method used

The vitrimer micro-crosslinked structure is constructed by twin-screw reactive extrusion, and combined with solid-phase shear milling technology, the inorganic filler is modified through silane coupling agent to achieve high dispersion and low heterogeneity, and the material performance is further optimized by hot pressing molding.

Benefits of technology

It realizes efficient dispersion and low heterogeneity of high-filled inorganic fillers in polymer matrix, improves the mechanical properties and functionality of composite materials, and expands its application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120310177A_ABST
    Figure CN120310177A_ABST
Patent Text Reader

Abstract

The invention provides a high-filling low-heterogeneity composite material with introduced vitrimer micro-crosslinking structure as well as a preparation method and application of the high-filling low-heterogeneity composite material with introduced vitrimer micro-crosslinking structure. According to the composite material, the vitrimer micro-crosslinking structure is constructed in a maleic anhydride grafted high-molecular polymer matrix by utilizing double-screw reactive extrusion; destructive compounding of the high-proportion silane coupling agent modified inorganic filler and a polymer matrix and damage to a vitrimer micro-crosslinked network are realized by utilizing a solid-phase shearing and grinding technology, then double-screw extrusion plasticizing granulation is utilized, and finally, the processes of forming and heterogeneity self-repairing are completed by virtue of hot press forming equipment. The characteristics of high dispersion and low heterogeneity of the inorganic filler in the polymer matrix are efficiently realized, and the synergism of functionality and mechanical properties of the highly-filled polymer matrix composite material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-filled inorganic filler / thermoplastic matrix composite materials, and relates to a high-filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, its preparation method and application. Specifically, it relates to a composite material that constructs a vitrimer micro-crosslinked structure in a high-filled inorganic filler / thermoplastic matrix system by reactive extrusion and realizes high filling, low heterogeneity and high dispersion of inorganic fillers, especially for the preparation using an industrial grinding disc-shaped solid-phase force chemical reactor disclosed in Chinese invention patent CN114534660B. Background Art

[0002] In the prior art, functional polymer composite materials use polymer polymers as platform materials, utilize their characteristics of easy processing and mixing at low temperatures, and then compound and mix inorganic / organic fillers with a specific filling ratio, so as to meet their functional characteristics other than mechanical properties, such as flame retardancy, structural stability, heat resistance and thermal stability. Generally speaking, by increasing the proportion of fillers in the system, synchronous improvement can be obtained in functional characteristics such as magnetism, electrochemistry performance, and thermal performance, that is, high-filled functional polymer composite materials are significantly superior to low-filled functional polymer composite materials in terms of functionality. However, in practical applications, the application routes of such functional polymer composite materials characterized by high filler filling have great limitations, and they are mostly used as masterbatches or special-purpose materials (such as artificial marble, resin-based brake materials). This is mainly because while such composite materials meet their functionality, it is difficult to simultaneously meet the high mechanical property requirements for their application routes.

[0003] Due to the existence of the above objective shortcomings, for such polymer-based composite materials with a high filler filling ratio (>50wt%), the scientific research community lacks systematic research, and the main focus is mostly on the dispersion problem of fillers at high filling ratios. By using processing equipment with better filler dispersion or through conventional modification methods, the dispersion degree of fillers is improved, and thus the mechanical properties of composite materials are enhanced.

[0004] Regarding the above research status, the inventors of the present invention believe that the dispersion of fillers, especially inorganic fillers, in the polymer matrix is undoubtedly of utmost importance. However, overemphasis on dispersion has overlooked the objective fact that the system is always a heterogeneous system after the compounding of the polymer matrix and inorganic fillers. How to solve or offset some of the heterogeneous characteristics brought about by inorganic fillers in the high-fill state is the next more important core problem to be solved for such high-fill polymer-based composites. At present, in the methods of dealing with the heterogeneity between inorganic particles and the polymer matrix, oven annealing and extending the hot pressing time are the main treatment means. However, in these two processes, only thermal vibrations of molecular chains exist in conventional polymer matrices, and there is no ability for intermolecular chain exchange. Therefore, oven annealing or extending the hot pressing time has little modification effect. For nylon and polyolefin semi-crystalline materials, the existence of crystalline regions means that at most only the molecular chains in the amorphous regions can move, slightly weakening the heterogeneity between inorganic particles and the matrix, with too low efficiency; while long-term hot pressing or oven treatment is prone to cause chain degradation due to long-term heating on the basis of the lack of effective movement of molecular chains.

[0005] Therefore, it is urgent to develop a new process technology for preparing polymer-based composites with high-fill characteristics. Under the condition of meeting the current trend of green environmental protection, while ensuring the high-dispersion behavior of fillers, it is necessary to weaken the influence of the high filling of inorganic fillers on the heterogeneity between the polymer matrix, further improve the mechanical properties of such composites, and expand their application fields. Summary of the Invention

[0006] In order to solve the above problems in the prior art, the present invention provides a high-fill and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, its preparation method and application. The composite material constructs a vitrimer micro-crosslinked structure in a maleic anhydride-grafted polymer matrix by twin-screw reactive extrusion, and uses the solid-phase shear milling technology to achieve the destructive compounding of a high-proportion silane coupling agent-modified inorganic filler and the polymer matrix and the destruction of the vitrimer micro-crosslinked network. Then, it uses twin-screw extrusion for plasticizing and pelletizing, and finally completes the forming and self-healing of heterogeneity with the help of a hot pressing forming device. It efficiently realizes the high dispersion and low-heterogeneity characteristics of inorganic fillers in the polymer matrix, and ensures the coordination of the functionality and mechanical properties of high-fill polymer-based composites.

[0007] To achieve the above object, the present invention adopts a technical solution composed of the following technical measures.

[0008] On the one hand, the present invention provides a preparation method for a high-fill and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, mainly including the following steps:

[0009] (1) Mix the raw materials including the following components evenly by mass parts to obtain mixture A:

[0010] 92 - 99 parts of maleic anhydride grafted polymer,

[0011] 0.5 - 3 parts of zinc acetylacetonate monohydrate,

[0012] 0.5 - 5 parts of liquid crosslinking agent;

[0013] The total of the maleic anhydride grafted polymer, zinc acetylacetonate monohydrate and liquid crosslinking agent is 100 parts;

[0014] Among them, the maleic anhydride grafted polymer is the product obtained by grafting modification of thermoplastic plastics with maleic anhydride, and the liquid crosslinking agent is selected from liquid crosslinking agents with multiple epoxy groups in its chemical structural formula;

[0015] (2) Use reactive extrusion to prepare intermediate composite pellets with an epoxy - based vitrimer micro - crosslinked structure from the mixture A obtained in step (1);

[0016] Among them, the process parameters of the reactive extrusion include: rotational speed 30 - 150 rpm, temperature 170 - 210 °C;

[0017] (3) Add silane coupling agent - modified inorganic filler to the intermediate composite pellets obtained in step (2) according to a mass ratio of 3:(6 - 8), and mix evenly to obtain mixture B;

[0018] (4) Add the mixture B obtained in step (3) into a disk - shaped solid - phase force chemical reactor for grinding and pulverization. After the grinding is completed, collect the composite powder; among them, the process parameters of the disk - shaped solid - phase force chemical reactor are: grinding pressure 3 - 6 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, circulating grinding 5 - 15 times, and the rotational speed of the disk is 50 - 200 revolutions per minute;

[0019] (5) Use reactive extrusion to prepare composite pellets from the composite powder obtained in step (4), which is a high - filled and low - heterogeneity composite material with an introduced vitrimer micro - crosslinked structure;

[0020] Among them, the process parameters of the reactive extrusion include: rotational speed 30 - 150 rpm, temperature 190 - 230 °C.

[0021] On the other hand, based on the above - prepared composite pellets, the present invention can prepare high - filled and low - heterogeneity composite products with an introduced vitrimer micro - crosslinked structure through conventional thermoplastic processing methods.

[0022] In this text, the maleic anhydride grafted polymer described in step (1) is the product obtained by grafting modification of thermoplastics with maleic anhydride. Generally speaking, the thermoplastics herein are the conventional thermoplastics selected in this technical field, such as polyethylene, polypropylene, polyolefin elastomer, ABS, etc. It should be noted that all such conventional thermoplastics can theoretically be grafted and modified with maleic anhydride to prepare maleic anhydride grafted polymers (or maleic anhydride grafted modified thermoplastics), and their sources can be self-made according to the references of the existing technical literature in this field, or directly obtained through commercial purchase.

[0023] In one technical solution, the maleic anhydride grafted polymer described in step (1) is preferably a maleic anhydride grafted polyolefin polymer.

[0024] To better illustrate the present invention and verify its technical effects, in one preferred technical solution, the maleic anhydride grafted polymer described in step (1) is maleic anhydride grafted high density polyethylene (HDPE-g-MA). It should be noted that the maleic anhydride grafted high density polyethylene can be obtained, for example, by directly purchasing the commercially available maleic anhydride grafted high density polyethylene raw material produced by Dow Chemical Company, or by directly referring to the conventional preparation method of maleic anhydride grafted polymers for self-making.

[0025] In one technical solution for reference, when the maleic anhydride grafted polymer described in step (1) is maleic anhydride grafted high density polyethylene (HDPE-g-MA) and is obtained by self-making under laboratory conditions, its preparation method mainly includes the following steps:

[0026] By weight, 97-99 parts of high density polyethylene (HDPE), 0.1-0.5 parts of peroxide initiator, and 1-3 parts of maleic anhydride (MA) are mixed evenly, and maleic anhydride grafted high density polyethylene is prepared by reactive extrusion;

[0027] Among them, the process parameters of the reactive extrusion include: rotation speed 170-200 rpm, temperature 180-230 °C.

[0028] In the above technical solution for reference, the high density polyethylene (HDPE) is a conventional raw material in the chemical industry, and those skilled in the art can directly obtain it through commercial purchase.

[0029] In the above technical solutions for reference, the peroxide initiator is selected from the peroxide initiators commonly used in the maleic anhydride graft modification process. Those skilled in the art can directly select a suitable peroxide initiator by referring to the maleic anhydride graft modification methods described in the prior art literature, such as any one of bis(tert-butylperoxyisopropyl)benzene (BIPB) and dicumyl peroxide.

[0030] In one of the technical solutions, based on the requirement of low cost, the liquid crosslinking agent in step (1) is preferably bisphenol A diglycidyl ether.

[0031] In this article, the reactive extrusion in step (2) is a technology that simultaneously completes chemical reactions and extrusion processing in an extruder for molding. Generally, a plasticizing and extrusion system composed of a screw and a barrel is used as the equipment for reactive extrusion. For example, it is processed using a twin-screw extruder, a triple-screw extruder, a planetary screw extruder, or other equipment capable of reactive extrusion that is common knowledge in the art.

[0032] In one of the technical solutions, based on the requirement of selecting more conventional industrial equipment, the reactive extrusion in step (2) is achieved by a twin-screw extruder.

[0033] In one of the preferred technical solutions, when the reactive extrusion in step (2) is achieved by a twin-screw extruder, the rotational speed in the process parameters of the reactive extrusion is 50 - 100 rpm.

[0034] In this article, the silane coupling agent-modified inorganic filler in step (3) is the product obtained by modifying conventional inorganic fillers with a silane coupling agent. Generally speaking, the inorganic filler is selected from the conventional inorganic fillers in this technical field, such as metal types, glass fiber types, calcium carbonate types, etc. It is preferably further a functional inorganic filler to exert the advantage of high filling of the present invention. It should be noted that in theory, all such conventional inorganic filler selections can be modified with a silane coupling agent to prepare a silane coupling agent-modified inorganic filler. At the same time, those skilled in the art can also match a suitable silane coupling agent based on the specific inorganic filler selected. Its source can be self-made by referring to the prior art literature in this field or directly obtained commercially.

[0035] In order to better illustrate the present invention and verify its technical effects, in one of the preferred technical solutions, the silane coupling agent-modified inorganic filler in step (3) is silane coupling agent-modified tungsten powder, so that the finally prepared composite material can be used as a raw material for nuclear shielding products. It should be noted that the silane coupling agent-modified tungsten powder can be obtained, for example, by directly purchasing commercially available silane coupling agent-modified tungsten powder raw materials, or by directly referring to conventional silane coupling agent modification methods for self-preparation.

[0036] In an even more preferred technical solution, in order to further reduce the filler heterogeneity in the high-density polyethylene / tungsten powder system, the silane coupling agent-modified inorganic filler in step (3) is silane coupling agent-modified tungsten powder, and the silane coupling agent used is a commercially available silane coupling agent with an amino functional group commonly used in the prior art, such as any one or more of KH550, KH560, and KH570. Its specific source can be obtained commercially or by self-preparation.

[0037] Among them, the disk-shaped solid-phase force chemical reactor in step (4) is the industrial disk-shaped solid-phase force chemical reactor disclosed in the prior invention patent CN114534660B of the applicant of the present invention.

[0038] It should be noted that this industrial disk-shaped solid-phase force chemical reactor is an industrial equipment finally improved based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9. It is significantly different from the structure of the laboratory prototype machine at the time of application of ZL95111258.9. A new disk structure is designed for industrial high-efficiency force chemical milling treatment. The disk is improved from the past vertical setting to a horizontal setting, and the disk size is greatly increased. Based on the horizontally set and large-sized disk, relevant fixed disk components and a hydraulic lifting system are innovatively designed, greatly improving its three-dimensional shear force.

[0039] Generally, the actual operation of the above-mentioned cyclic milling process is to mill the material through the disk-shaped solid-phase force chemical reactor, collect the product at the discharge end, and then place it in the disk-shaped solid-phase force chemical reactor again for milling treatment. The above process is regarded as 1 cycle of cyclic milling.

[0040] In this article, in step (4), circulating cooling liquid at 15 - 35 °C is introduced to control the temperature of the disk surface of the mill, and the cooling liquid is water, ethylene glycol, or glycerol.

[0041] It should be noted that among the process parameters of the reactive extrusion in step (5), the rotation speed will affect the degree of damage to the vitrimer micro-crosslinked network, thus directly affecting the mechanical properties of the products prepared by subsequent conventional thermoplastic forming processes.

[0042] In this article, based on the above-prepared composite pellets, a highly filled and low-heterogeneity composite product incorporating a vitrimer micro-crosslinked structure can be prepared by conventional thermoplastic processing methods. For example, a highly filled and low-heterogeneity composite product can be prepared by hot pressing. The specific thermoplastic processing method and process parameters can be directly determined according to the conventional thermoplastic process methods and process parameters of the selected maleic anhydride-grafted polymer (or the polymer selected from the maleic anhydride-grafted polymer).

[0043] On the other hand, the present invention also provides a functional composite board made of the above-mentioned highly filled and low-heterogeneity composite material incorporating a vitrimer micro-crosslinked structure, which is characterized in that the functional composite board is prepared by hot pressing the highly filled and low-heterogeneity composite material including the vitrimer micro-crosslinked structure.

[0044] To better illustrate the present invention and verify its technical effects, in one of the preferred technical solutions, when the maleic anhydride-grafted polymer is maleic anhydride-grafted high-density polyethylene and the silane-coupling-agent-modified inorganic filler is silane-coupling-agent-modified tungsten powder, a nuclear shielding composite board is prepared by hot pressing the composite pellets. The process parameters of the hot pressing include: pressure 10 - 20 MPa, temperature 160 - 230 °C, and hot pressing time 10 min - 12 h.

[0045] It should be noted that in the technical solution of the present invention, the high dispersion of highly filled inorganic powders in the polymer matrix is similar to that reported previously. The two phases have similar polarities, and the use of strong shear force can achieve the efficient dispersion of inorganic powders in the polymer matrix. Therefore, in the present invention, the polymer is maleic anhydrified to enhance its polarity, and at the same time, the inorganic filler is modified with a silane coupling agent to reduce its polarity. This step is consistent with most surface modification methods. However, the present invention innovatively reacts the maleic anhydride groups grafted on the polymer with the amino and epoxy groups on the surface of the silane-coupling-agent-modified inorganic filler to enhance the interfacial strength. Generally speaking, this interfacial reaction requires the addition of a catalyst, rather than just relying on high heat to achieve it. In addition, the difficulty of the interfacial reaction needs to be considered. The degree of reaction between such inorganic and organic matrices is very low, not only because the hydroxyl content on the surface of the inorganic filler is not high and cannot react with the silane coupling agent to a high degree, but also because the heterogeneity is too strong and the reaction barrier is high. Therefore, a certain amount of additional crosslinking agent needs to be introduced to promote the degree of the interfacial reaction by utilizing the high-temperature transesterification ability, and to promote the global movement of the polymer matrix molecular chains in the thermal field by utilizing the transesterification ability, enhancing the ability of molecular chain exchange and diffusion, and weakening the internal stress of the polymer matrix to eliminate part of the heterogeneity.

[0046] Through comparative experiments by the inventors of the present invention, it was found that for the product obtained by twin-screw co-blending granulation and then pressing of maleic anhydride grafted polymer and silane coupling agent modified inorganic filler, although the product has good processing fluidity and good dispersion of inorganic filler, the mechanical properties of the product are still very poor. The core reason is that the strong heterogeneity brought about by high filling of inorganic filler leads to poor mechanical properties of the high-filled polymer matrix composite. When tungsten powder is selected as the inorganic filler, the γ-ray shielding effect of the obtained sample material is not good either. The detection of the three core properties (dispersion, mechanical properties, γ-ray shielding effect) is weaker than the performance of the sample prepared according to the present invention patent.

[0047] After being processed by the twin-screw reactive extrusion process, due to its powerful shear destruction force field, the twin-screw extruder can control the degree of maleic anhydride grafting reaction, control the degree of construction of the vitrimer micro-crosslinked structure, and effectively control the retention-destruction degree of the vitrimer micro-crosslinked network during the plasticization of composite pellets through a convenient screw speed design. During the subsequent hot pressing process, different hot pressing times will show different changes in the crystallinity of the high-filled and low-heterogeneity composite material.

[0048] Through research by the inventors of the present invention, it was found that under the powerful destruction force field of solid-phase grinding, the conventional maleic anhydride grafted polymer particles are fully destroyed and change from granular to flat. In this process, the force destroys the vitrimer micro-crosslinked network structure, and during the subsequent twin-screw thermoplastic granulation, the influence of crosslinking bonds on fluidity can be weakened; when co-grinding with silane coupling agent modified inorganic filler, the inorganic filler particles will adhere to the maleic anhydride grafted polymer particles in a large area. At the same time, during the destructive dispersion and compounding process at room temperature solid phase, the inorganic filler particles can be fully promoted to embed into the polymer matrix, weakening the existence of the polymer agglomeration area that is difficult to melt after being modified by vitrimer during twin-screw plasticization, and realizing the full combination of inorganic filler and polymer. At the same time, according to the SEM results, the role of solid-phase shear grinding in high-filled and low-heterogeneity composite materials was verified (attached to the specification Figure 2 ).

[0049] During the hot pressing process, for high-thickness polymer material products, it is a stable and common production and manufacturing process. For thick plates and polymer matrix composites with high viscosity, the hot pressing time is often long. In the conventional production process, the heat for a long time is not efficiently utilized, and it is only to ensure the melting and forming of thick plate products. However, according to the solution described in the present invention patent, during the long-term hot pressing process, the heat source can promote the transesterification of the vitrimer micro-crosslinked network, thereby inducing the global movement of molecular chains, realizing strong exchange and diffusion between molecular chains, weakening the heterogeneity and internal stress of the polymer matrix caused by the presence of inorganic filler, and it can be verified according to the AFM test results (attached to the specification Figure 3) This ensures higher service performance of the product.

[0050] Based on the above description, in one of the preferred technical solutions, the composite pellets are prepared into a high-fill low-heterogeneity composite product by hot pressing, where the hot pressing time is 60 - 120 min.

[0051] Considering the above conditions, the high-fill low-heterogeneity composite material prepared according to the technical solution of the present invention realizes the synergistic optimization of high mechanical properties and functionality, and has excellent commercial value.

[0052] Referring to one of the technical solutions of the present invention, the mechanical properties of the toughened 70wt% tungsten powder high-fill HDPE-based composite sample are as follows: the strength is 22.74%, and the elongation is 192.1%, which are superior to those of the comparative sample HDPE-g-MA / W, whose strength is 26.8 MPa and elongation is 24.2%.

[0053] Generally, in addition to the catalyst and crosslinking agent, the present invention can also add other processing aids such as antioxidants, flame retardants, and anti-aging agents known in the prior art. However, the premise is that these processing aids shall not have an adverse effect on the achievement of the purpose of the present invention and the obtaining of the excellent effects of the present invention.

[0054] The present invention has the following beneficial effects:

[0055] (1) The present invention provides a high-fill low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, its preparation method and application. By using reactive extrusion to construct a vitrimer micro-crosslinked structure in the polymer matrix, it not only realizes the efficient dispersion of high-fill inorganic fillers, but also first proposes a solution to weaken the heterogeneity of high-fill inorganic filler / polymer-based composites, improves their mechanical properties, enhances the functions of the composites (such as γ-ray shielding effect), and ensures the service performance of the composites.

[0056] (2) The present invention utilizes the existence of the vitrimer micro-crosslinked network to induce the improvement of the interfacial strength between the polymer matrix and inorganic filler particles, and induces the transesterification reaction of the vitrimer micro-crosslinked network during thermoplastic processing, such as by long-time hot pressing treatment, and drives the global movement of polymer molecular chains, enhances the diffusion and exchange ability between molecular chains, promotes the self-correction process of the polymer matrix, and alleviates the heterogeneity of the composite material.

[0057] (3) The present invention effectively promotes the intercalation of inorganic fillers and maleic anhydride-grafted polymer particles by using solid-state shear milling technology, and suppresses the subsequent reactive extrusion plasticization stage by using room-temperature solid-state compounding. It breaks the vitrimer cross-linking network existing in the maleic anhydride-grafted polymer particles due to the viscosity region difference of the polymer after vitrimer modification, bringing convenience to the subsequent processing process.

[0058] (4) Based on reactive extrusion technology, vitrimer micro-crosslinking construction technology, and solid-state shear technology, the present invention has the advantages of simple production process, easy operation, batch and continuous production, and is suitable for the preparation of conventional high-filled polymer-based composite products, with obvious commercial promotion advantages. Description of the Drawings

[0059] Figure 1 SEM and TEM photos of the quenched cross-section of the nuclear shielding composite board prepared in Example 1 of the present invention. Among them, from left to right are the SEM photo of the quenched cross-section of the nuclear shielding composite board prepared in Example 1, the magnified SEM photo, the TEM photo, and the magnified TEM photo.

[0060] Figure 2 SEM photo of the composite powder obtained in step (3) of Example 1 of the present invention.

[0061] Figure 3 Comparison chart of AFM modulus distribution of the cross-sections of the nuclear shielding composite boards prepared in Examples 1-4 of the present invention.

[0062] Among them, 20 min corresponds to the nuclear shielding composite board prepared in Example 1; 1 h corresponds to the nuclear shielding composite board prepared in Example 2; 2 h corresponds to the nuclear shielding composite board prepared in Example 3; 6 h corresponds to the nuclear shielding composite board prepared in Example 1.

[0063] Figure 4 Column chart of the tensile strength comparison of the samples prepared in Examples 1-20 and Comparative Example 1 of the present invention.

[0064] Among them, 1%-30 rpm corresponds to the samples of Examples 1-4, 1%-80 rpm corresponds to the samples of Examples 5-8, 1%-130 rpm corresponds to the samples of Examples 9-12, 0.5%-80 rpm-4 MPa corresponds to the samples of Examples 13-16, 0.5%-130 rpm-5 MPa corresponds to the samples of Examples 17-20, and HDPE-g-MA+W corresponds to the sample of Comparative Example 1.

[0065] Figure 5 Line graph of the elongation rate comparison of the samples prepared in Examples 1-20 and Comparative Example 1 of the present invention.

[0066] Among them, 1% - 30 rpm corresponds to the samples of Examples 1 - 4, 1% - 80 rpm corresponds to the samples of Examples 5 - 8, 1% - 130 rpm corresponds to the samples of Examples 9 - 12, 0.5% - 80 rpm - 4 MPa corresponds to the samples of Examples 13 - 16, 0.5% - 130 rpm - 5 MPa corresponds to the samples of Examples 17 - 20, and HDPE-g-MA + W corresponds to the sample of Comparative Example 1.

[0067] Figure 6 It is a column chart comparing the gamma-ray shielding effects of the samples prepared in Example 17, Example 20, and Comparative Example 1. Among them, No shielding corresponds to the blank sample, HDPE-g-MA / W corresponds to the sample of Comparative Example 1, 0.5% - 20 min corresponds to the sample of Example 17, and 0.5% - 6 h corresponds to the sample of Example 20. Detailed implementation manners

[0068] To further understand the present invention, the preferred implementation manners of the present invention will be described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve the purpose. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred examples, and those skilled in the art can obviously make changes, or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art are fully aware of the following terms, the following definitions are still presented to help illustrate the subject matter disclosed in the present invention.

[0069] In one aspect, the present invention provides a method for preparing a highly filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, which mainly includes the following steps:

[0070] (1) By mass, mix the following components of raw materials evenly to obtain a mixture A:

[0071] Maleic anhydride grafted high molecular polymer: 92 - 99 parts,

[0072] Zinc acetylacetonate monohydrate: 0.5 - 3 parts,

[0073] Liquid crosslinking agent: 0.5 - 5 parts;

[0074] The total of the maleic anhydride grafted high molecular polymer, zinc acetylacetonate monohydrate, and liquid crosslinking agent is 100 parts;

[0075] Among them, the maleic anhydride grafted polymer is a product obtained by grafting and modifying a thermoplastic with maleic anhydride, and the liquid crosslinking agent is selected from liquid crosslinking agents having multiple epoxy groups in its chemical structural formula;

[0076] (2) The mixture A obtained in step (1) is prepared by reactive extrusion to obtain an intermediate composite pellet with an epoxy vitrimer micro-crosslinked structure;

[0077] Among them, the process parameters of the reactive extrusion include: rotation speed 30 - 150 rpm, temperature 170 - 210 °C;

[0078] (3) A silane coupling agent modified inorganic filler is added to the intermediate composite pellet obtained in step (2) according to a mass ratio of 3:(6 - 8), and after mixing evenly, it is used as mixture B;

[0079] (4) The mixture B obtained in step (3) is added to a disk-shaped solid-state mechanical chemical reactor for grinding and pulverization. After the grinding is completed, the composite powder is collected; among them, the process parameters of the disk-shaped solid-state mechanical chemical reactor are: grinding pressure 3 - 6 MPa, the temperature of the disk surface of the grinding disk is controlled at 15 - 35 °C by introducing circulating cooling liquid, circulating grinding 5 - 15 times, and the rotation speed of the grinding disk 50 - 200 revolutions per minute;

[0080] (5) The composite powder obtained in step (4) is prepared by reactive extrusion to obtain a composite pellet, which is a high-filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure;

[0081] Among them, the process parameters of the reactive extrusion include: rotation speed 30 - 150 rpm, temperature 190 - 230 °C.

[0082] On the other hand, based on the above-prepared composite pellet, the present invention can prepare a high-filled and low-heterogeneity composite product introducing a vitrimer micro-crosslinked structure by a conventional thermoplastic processing method.

[0083] In this article, the maleic anhydride grafted polymer in step (1) is a product obtained by grafting and modifying a thermoplastic with maleic anhydride. Generally speaking, the thermoplastic is a conventional thermoplastic selected in the technical field. In one embodiment, for example, it includes polyethylene, polypropylene, polyolefin elastomer, ABS, etc. It should be noted that all such conventional thermoplastic selections can theoretically be grafted and modified with maleic anhydride to prepare a maleic anhydride grafted polymer (or maleic anhydride grafted and modified thermoplastic), and its source can be prepared by oneself according to the reference of the existing technical literature in the field, or directly obtained commercially.

[0084] In one of the embodiments, the maleic anhydride grafted high molecular polymer in step (1) is preferably a maleic anhydride grafted polyolefin polymer.

[0085] To better illustrate the present invention and verify its technical effects, in one of the preferred embodiments, the maleic anhydride grafted high molecular polymer in step (1) is maleic anhydride grafted high density polyethylene (HDPE-g-MA). It should be noted that the maleic anhydride grafted high density polyethylene can be obtained, for example, by directly purchasing the commercially available maleic anhydride grafted high density polyethylene raw material produced by Dow Chemical Company, or by directly referring to the conventional preparation method of maleic anhydride grafted polymers for self-production.

[0086] In one of the reference embodiments, when the maleic anhydride grafted high molecular polymer in step (1) is maleic anhydride grafted high density polyethylene (HDPE-g-MA) and is obtained by self-production under laboratory conditions, its preparation method mainly includes the following steps:

[0087] By weight, 97-99 parts of high density polyethylene (HDPE), 0.1-0.5 parts of peroxide initiator, and 1-3 parts of maleic anhydride (MA) are mixed evenly, and maleic anhydride grafted high density polyethylene is prepared by reactive extrusion;

[0088] Among them, the process parameters of the reactive extrusion include: rotation speed 170-200 rpm, temperature 180-230 °C.

[0089] In the above reference embodiment, the high density polyethylene (HDPE) is a conventional raw material in the chemical industry, and those skilled in the art can directly obtain it through the market.

[0090] In the above reference embodiment, the peroxide initiator is selected from the peroxide initiators commonly used in the maleic anhydride grafting modification process. Those skilled in the art can directly refer to the maleic anhydride grafting modification methods recorded in the existing technical literature to select a suitable peroxide initiator, such as any one of bis(tert-butylperoxyisopropyl)benzene (BIPB) and dicumyl peroxide.

[0091] In one of the embodiments, based on the low-cost requirement, the liquid crosslinking agent in step (1) is preferably bisphenol A diglycidyl ether.

[0092] In this text, the reactive extrusion described in step (2) is a technology that simultaneously completes chemical reactions and extrusion processing in an extruder for shaping and processing. Generally, a plasticizing and extrusion system composed of a screw and a barrel is used as the equipment for reactive extrusion. In one embodiment, for example, a twin-screw extruder, a triple-screw extruder, a planetary screw extruder, or other equipment capable of reactive extrusion in the common general knowledge in this field is used for processing.

[0093] In one embodiment, based on the need to select more conventional industrial equipment, the reactive extrusion described in step (2) is achieved by a twin-screw extruder.

[0094] In one preferred embodiment, when the reactive extrusion described in step (2) is achieved by a twin-screw extruder, the rotational speed in the process parameters of the reactive extrusion is 50 - 100 rpm.

[0095] In this text, the silane-coupling-agent-modified inorganic filler described in step (3) is the product obtained by modifying conventional inorganic fillers with a silane coupling agent. Generally speaking, the inorganic fillers are selected from the conventional inorganic fillers in this technical field. In one embodiment, for example, they include metal types, glass fiber types, calcium carbonate types, etc., and are preferably further functional inorganic fillers to exert the advantages of high filling of the present invention. It should be noted that in theory, all such conventional inorganic filler selections can be modified with a silane coupling agent to prepare the silane-coupling-agent-modified inorganic filler. At the same time, those skilled in the art can also match a suitable silane coupling agent based on the specific inorganic filler selected. Its source can be self-made according to the reference of the existing technical literature in this field or directly obtained commercially.

[0096] To better illustrate the present invention and verify its technical effects, in one preferred embodiment, the silane-coupling-agent-modified inorganic filler described in step (3) is silane-coupling-agent-modified tungsten powder, so that the finally prepared composite material can be used as the raw material for nuclear shielding products. It should be noted that the silane-coupling-agent-modified tungsten powder can be obtained, for example, by directly purchasing commercially available raw materials of silane-coupling-agent-modified tungsten powder or directly preparing it by referring to conventional silane coupling agent modification methods.

[0097] In an even more preferred embodiment, in order to further reduce the filler heterogeneity in the high-density polyethylene / tungsten powder system, the silane-coupling-agent-modified inorganic filler described in step (3) is silane-coupling-agent-modified tungsten powder, and the silane coupling agent used is a commercially available silane coupling agent with an amino functional group that is common in the prior art, such as any one or more of KH550, KH560, and KH570. Its specific source can be obtained commercially or prepared by self-making.

[0098] Among them, the disk-shaped solid-phase force chemical reactor described in step (4) is the industrial disk-shaped solid-phase force chemical reactor disclosed in the prior invention patent CN114534660B of the applicant of the present invention.

[0099] It should be noted that this industrial disk-shaped solid-phase force chemical reactor is an industrial equipment finally improved based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9. It is significantly different from the structure of the laboratory prototype at the time of the application of ZL95111258.9. A new disk structure is designed for industrial high-efficiency force chemical milling treatment. It is improved from the vertical setting of the original disk to the horizontal setting, and the disk size is greatly increased. Based on the horizontally set and large-sized disk, relevant fixed disk components and hydraulic lifting systems are innovatively designed, greatly improving its three-dimensional shear force.

[0100] Generally, the actual operation of the above-mentioned cyclic milling process is to mill the material through the disk-shaped solid-phase force chemical reactor, collect the product at the discharge end, and then place it in the disk-shaped solid-phase force chemical reactor again for milling treatment. The above process is regarded as 1 cycle of cyclic milling.

[0101] In this article, in step (4), circulating cooling liquid at 15-35 °C is introduced to control the temperature of the disk surface of the mill. The cooling liquid is water, ethylene glycol or glycerol.

[0102] It should be noted that among the process parameters of the reactive extrusion described in step (5), the rotation speed will affect the degree of damage of the vitrimer micro-crosslinked network, thus directly affecting the mechanical properties of the products prepared by the subsequent conventional thermoplastic forming process.

[0103] In this article, based on the above-prepared composite pellets, high-filled and low-heterogeneity composite products introducing the vitrimer micro-crosslinked structure can be prepared by conventional thermoplastic processing methods. For example, high-filled and low-heterogeneity composite products can be prepared by hot pressing. The specific thermoplastic processing methods and process parameter selection can be directly based on the conventional thermoplastic process methods and process parameters of the maleic anhydride grafted polymer (or the polymer selected in the maleic anhydride grafted polymer).

[0104] On the other hand, the present invention also provides a functional composite board using the above high-filled and low-heterogeneity composite material introducing the vitrimer micro-crosslinked structure, which is characterized in that the high-filled and low-heterogeneity composite material including the vitrimer micro-crosslinked structure is prepared into a functional composite board by hot pressing.

[0105] In order to better illustrate the present invention and verify its technical effects, in one preferred embodiment, when the maleic anhydride grafted polymer is maleic anhydride grafted high density polyethylene and the silane coupling agent modified inorganic filler is silane coupling agent modified tungsten powder, the nuclear shielding composite board is prepared by hot pressing the composite pellets. The process parameters of the hot pressing include: pressure 10 - 20 MPa, temperature 160 - 230 °C, and hot pressing time 10 min - 12 h.

[0106] It should be noted that in the technical solution of the present invention, the realization of high dispersion of highly filled inorganic powders in the polymer matrix is similar to that reported by predecessors. The two phases have similar polarities, and the use of strong shear force can achieve the efficient dispersion of inorganic powders in the polymer matrix. Therefore, in the present invention, the polymer is maleic anhydrified to enhance its polarity, and at the same time, the inorganic filler is modified with a silane coupling agent to reduce its polarity. This step is consistent with most surface modification methods. However, the present invention innovatively reacts the maleic anhydride groups grafted on the polymer with the amino and epoxy groups on the surface of the silane coupling agent modified inorganic filler to enhance the interfacial strength. Generally speaking, this interfacial reaction requires the addition of a catalyst, rather than just relying on high heat to achieve. In addition, the difficulty of the interfacial reaction needs to be considered. The degree of reaction between such inorganic and organic matrices is very low, not only because the hydroxyl content on the surface of the inorganic filler is not high and cannot react with the silane coupling agent to a high degree, but also because of the excessive heterogeneity and high reaction barrier; therefore, a certain amount of additional cross-linking agent needs to be introduced to promote the degree of the interfacial reaction by utilizing the high-temperature transesterification ability and to promote the global movement of the molecular chains in the polymer matrix under the thermal field by utilizing the transesterification ability, enhancing the ability of molecular chain exchange and diffusion, and weakening the internal stress of the polymer matrix and eliminating part of the heterogeneity.

[0107] Through comparative experiments by the inventors of the present invention, it is found that for the product obtained by double-screw co-blending and pelletizing the maleic anhydride grafted polymer and the silane coupling agent modified inorganic filler and then pressing the board, although the processing fluidity of the product is good and the inorganic filler is well dispersed, the mechanical properties of the product are still very poor. The core reason is that the strong heterogeneity brought about by the high filling of the inorganic filler leads to poor mechanical properties of the highly filled polymer-based composite material. When the inorganic filler is tungsten powder, the γ-ray shielding effect of the obtained sample material is also not good. The detection of the three core properties (dispersion, mechanical properties, γ-ray shielding effect) is weaker than the performance of the sample prepared according to the present invention patent.

[0108] After being processed by the twin-screw reactive extrusion process, due to its powerful shear destruction force field, the twin-screw extruder can control the degree of maleic anhydride grafting reaction, control the degree of construction of the vitrimer micro-crosslinked structure, and effectively control the retention-destruction degree of the vitrimer micro-crosslinked network during the plasticization of the composite pellets through a convenient screw speed design. During the subsequent hot pressing process, different hot pressing times will show different changes in the crystallinity of the highly filled and low-heterogeneity composite materials.

[0109] The inventors of the present invention have found that under the powerful destruction force field of solid-phase milling, the conventional maleic anhydride-grafted polymer particles are fully destroyed and changed from granular to flat. In this process, the force destroys the vitrimer micro-crosslinked network structure. During the subsequent twin-screw thermoplastic granulation, the influence of crosslinking bonds on fluidity can be weakened; when co-milled with silane coupling agent-modified inorganic fillers, the inorganic filler particles will adhere to the maleic anhydride-grafted polymer particles in a large area. At the same time, during the destructive dispersion and compounding process at room temperature in the solid phase, the inorganic filler particles can be fully promoted to embed into the polymer matrix, weakening the existence of the polymer agglomeration area that is difficult to melt after being modified by vitrimer during twin-screw plasticization, and realizing the full combination of inorganic fillers and polymer. At the same time, according to the SEM results, the role of solid-phase shear milling in highly filled and low-heterogeneity composite materials is verified (see attached Figure 2 ).

[0110] During the hot pressing process, for high-thickness polymer material products, it is a stable and common manufacturing process. For thick plates and polymer matrix composites with high viscosity, the hot pressing time is often long. In the conventional production process, the heat for a long time is not efficiently utilized, and only to ensure the melting and forming of thick plate products. However, according to the scheme described in the present invention patent, during the long-time hot pressing process, the heat source can promote the transesterification of the vitrimer micro-crosslinked network, thereby inducing the global movement of molecular chains, realizing strong exchange and diffusion between molecular chains, weakening the heterogeneity and internal stress of the polymer matrix caused by the presence of inorganic fillers, and can be verified according to the AFM test results (see attached Figure 3 ), ensuring higher service performance of the products.

[0111] Based on the above description, in one of the preferred embodiments, the composite pellets are prepared into highly filled and low-heterogeneity composite products by hot pressing molding, where the hot pressing time is 60 - 120 min.

[0112] Based on the above conditions, therefore, the highly filled and low-heterogeneity composite materials prepared by referring to the embodiments of the present invention achieve the synergistic optimization of higher mechanical properties and functionality, and have excellent commercial value.

[0113] Referring to one embodiment of the present invention, the mechanical properties of the toughened 70wt% tungsten powder highly filled HDPE-based composite sample obtained are as follows: the strength is 22.74% and the elongation at break is 192.1%, which are superior to those of the comparative sample HDPE-g-MA / W, whose strength is 26.8 MPa and elongation at break is 24.2%.

[0114] Generally, in addition to the catalyst and crosslinking agent, other processing aids such as antioxidants, flame retardants, and anti-aging agents well-known in the prior art can also be added to the present invention. However, the prerequisite is that these processing aids shall not have an adverse effect on the achievement of the purpose of the present invention and the attainment of its excellent effects.

[0115] The present application will be further explained in detail with reference to the examples below. However, those skilled in the art should understand that these examples are provided for illustrative purposes only and are not intended to limit the present application.

[0116] Examples

[0117] The embodiments of the present application will be described in detail below in conjunction with the examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. For those not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. For those reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase. The present application should not be construed as being limited to the specific examples described.

[0118] 1. Raw materials

[0119] Absolute ethanol, zinc acetylacetonate monohydrate, bisphenol A diglycidyl ether, from Chengdu Kelong Chemical Co., Ltd.

[0120] Silane coupling agent-modified tungsten powder (modified with KH560), from Shanghai Xiangtian Nanomaterials Co., Ltd.

[0121] Maleic anhydride-grafted high-density polyethylene, HDPE-g-MA, Dow GR204

[0122] Tungsten powder, 1 - 3 μm, from Shanghai Xiangtian Nanomaterials Co., Ltd.

[0123] 2. Preparation method

[0124] (1) By mass fraction, the following components of raw materials are mixed evenly to obtain mixture A:

[0125] Maleic anhydride-grafted high-density polyethylene 98 - 98.5 parts,

[0126] Zinc acetylacetonate monohydrate 1 part,

[0127] Bisphenol A diglycidyl ether 0.5 - 1 part;

[0128] (2) Reactively extrude the mixture A obtained in step (1) using a twin-screw extruder to prepare an intermediate composite pellet with an epoxy-based vitrimer micro-crosslinked structure;

[0129] Among them, the process parameters of the reactive extrusion include: rotation speed 50 rpm, temperature 180 - 200 °C;

[0130] (3) Add silane coupling agent-modified tungsten powder to the intermediate composite pellet obtained in step (2) according to a mass ratio of 3:7, and mix evenly to obtain mixture B;

[0131] (4) Add the mixture B obtained in step (3) to a disk-shaped solid-state reactive grinding reactor for grinding and pulverization. After the grinding is completed, collect the composite powder; among them, the process parameters of the disk-shaped solid-state reactive grinding reactor are: grinding pressure 3 - 5 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, circulate and grind 10 times, and the rotation speed of the disk is 50 - 150 revolutions per minute;

[0132] (5) Reactively extrude the composite powder obtained in step (4) using a twin-screw extruder to prepare a composite pellet, which is a high-filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure;

[0133] Among them, the process parameters of the reactive extrusion include: rotation speed 30 - 130 rpm, temperature 190 - 230 °C.

[0134] To verify the technical effects of the present invention, a nuclear shielding composite board is prepared by hot pressing the composite pellet as a sample. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200 °C, hot pressing time 20 min - 360 min.

[0135] 3. Testing methods

[0136] In the examples, a scanning electron microscope (SEM) is used to examine the dispersion of tungsten powder in the quenched section of the composite material sample.

[0137] A transmission electron microscope (TEM) is used to examine the dispersion of tungsten powder in the matrix.

[0138] A differential scanning calorimeter (DSC) is used to detect the change in crystallinity of the samples under different hot pressing times.

[0139] An atomic force microscope (AFM) is used to detect the modulus distribution of the cross-section of the composite material sample.

[0140] The mechanical property test follows the ASTM D 412 standard, and the running speed of the chuck is 50 mm / min.

[0141] Example 1

[0142] Example 1 is prepared according to the steps of the above-mentioned "2. Preparation method". In step (1), 98 parts of maleic anhydride grafted high-density polyethylene and 1 part of bisphenol A diglycidyl ether are used; in step (4), the process parameters of the disk-shaped solid-phase force chemical reactor are as follows: the grinding pressure is 3 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, the cyclic grinding is carried out 10 times, and the disk rotation speed is 50 revolutions per minute; in step (5), the process parameters of the reactive extrusion include: rotation speed 30 rpm, temperature 190 - 230 °C; finally, a composite granule is prepared, which is a high-fill low-heterogeneity composite material introducing the vitrimer micro-crosslinked structure.

[0143] To verify the technical effect of this example, the composite granule is prepared into a nuclear shielding composite board as a sample by hot pressing. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200 °C, and hot pressing time 20 min.

[0144] The prepared nuclear shielding composite board has a tensile strength of 31.5 MPa, an elongation rate of 39.8%, and a shielding effect full-energy peak count of 621.8 s -1 。

[0145] Example 2

[0146] Example 2 is based on the steps of Example 1, and finally a composite granule is prepared, which is a high-fill low-heterogeneity composite material introducing the vitrimer micro-crosslinked structure.

[0147] To verify the technical effect of this example, the composite granule is prepared into a nuclear shielding composite board as a sample by hot pressing. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200 °C, and hot pressing time 60 min.

[0148] The prepared nuclear shielding composite board has a tensile strength of 32.1 MPa, an elongation rate of 32.4%, and a shielding effect full-energy peak count of 621.7 s -1 。

[0149] Example 3

[0150] Example 3 is based on the steps of Example 1, and finally a composite granule is prepared, which is a high-fill low-heterogeneity composite material introducing the vitrimer micro-crosslinked structure.

[0151] To verify the technical effect of this example, the composite granule is prepared into a nuclear shielding composite board as a sample by hot pressing. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200 °C, and hot pressing time 120 min.

[0152] The prepared nuclear shielding composite plate has a tensile strength of 27.6 MPa, an elongation of 54.6%, and a shielding effect full energy peak count of 621.7 s -1 .

[0153] Example 4

[0154] Example 4 is based on the steps of Example 1, and finally prepares composite granules, that is, a high-filling, low-heterogeneity composite material with a vitrimer micro-cross-linked structure.

[0155] In order to verify the technical effect of this embodiment, the composite granules were prepared by hot pressing to obtain a nuclear shielding composite plate as a sample. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200° C., and hot pressing time 360 min.

[0156] The prepared nuclear shielding composite plate has a tensile strength of 27.3 MPa, an elongation of 117.8%, and a shielding effect full energy peak count of 620.7 s -1 .

[0157] Embodiments 5 to 8

[0158] Examples 5 to 8 are in accordance with the above-mentioned "2. Preparation method" steps, wherein in step (1), the amount of maleic anhydride grafted high-density polyethylene is 98 parts, and the amount of bisphenol A diglycidyl ether is 1 part; in step (4), the process parameters of the disc-shaped solid phase force chemical reactor are: the grinding pressure is 3 MPa, the temperature of the disc surface is controlled at 15 to 35°C by introducing circulating cooling liquid, the grinding cycle is repeated 10 times, and the disc speed is 50 rpm; the process parameters of the reactive extrusion in step (5) include: a speed of 80 rpm and a temperature of 190 to 230°C; and finally, a composite pellet is prepared, which is a high-filling, low-heterogeneity composite material with a vitrimer micro-crosslinked structure.

[0159] To verify the technical effects of Examples 5 to 8, the composite granules were prepared into nuclear shielding composite plates as samples by hot pressing. The process parameters of the hot pressing include: pressure 15 MPa, temperature 200°C, hot pressing time 20 min, 60 min, 120 min, and 360 min, respectively corresponding to Example 5, Example 6, Example 7, and Example 8.

[0160] The nuclear shielding composite plates prepared in Examples 5 to 8 have a tensile strength of 22-26 MPa, an elongation of about 32.4%, and a shielding effect full energy peak count of 621.7 s -1 about.

[0161] Examples 9 to 12

[0162] Examples 9 to 12 are prepared according to the steps of the above-mentioned "2. Preparation Method". In step (1), 98 parts of maleic anhydride grafted high-density polyethylene and 1 part of bisphenol A diglycidyl ether are used. In step (4), the process parameters of the disk-shaped solid-state mechanical chemical reactor are as follows: the grinding pressure is 3 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, the cyclic grinding is carried out 10 times, and the rotational speed of the disk is 50 revolutions per minute. In step (5), the process parameters of the reactive extrusion include: the rotational speed is 130 rpm, and the temperature is 190 - 230 °C. Finally, composite pellets are prepared, which are high-fill low-heterogeneity composites introducing vitrimer micro-crosslinked structures.

[0163] To verify the technical effects of Examples 9 to 12, nuclear shielding composite plates are prepared by hot pressing the composite pellets as samples. The process parameters of the hot pressing include: the pressure is 15 MPa, the temperature is 200 °C, and the hot pressing times are 20 min, 60 min, 120 min, and 360 min corresponding to Example 9, Example 10, Example 11, and Example 12 in sequence.

[0164] For the nuclear shielding composite plates prepared in Examples 9 to 12, the tensile strength is between 22 - 28 MPa, the elongation is about 40 - 80%, and the shielding effect full-energy peak count is 622.3 s -1 or so.

[0165] Examples 13 to 16

[0166] Examples 13 to 16 are prepared according to the steps of the above-mentioned "2. Preparation Method". In step (1), 98.5 parts of maleic anhydride grafted high-density polyethylene and 0.5 part of bisphenol A diglycidyl ether are used. In step (4), the process parameters of the disk-shaped solid-state mechanical chemical reactor are as follows: the grinding pressure is 4 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, the cyclic grinding is carried out 10 times, and the rotational speed of the disk is 100 revolutions per minute. In step (5), the process parameters of the reactive extrusion include: the rotational speed is 80 rpm, and the temperature is 190 - 230 °C. Finally, composite pellets are prepared, which are high-fill low-heterogeneity composites introducing vitrimer micro-crosslinked structures.

[0167] To verify the technical effects of Examples 13 to 16, nuclear shielding composite plates are prepared by hot pressing the composite pellets as samples. The process parameters of the hot pressing include: the pressure is 15 MPa, the temperature is 200 °C, and the hot pressing times are 20 min, 60 min, 120 min, and 360 min corresponding to Example 13, Example 14, Example 15, and Example 16 in sequence.

[0168] The nuclear shielding composite plates prepared in Examples 13 to 16 have a tensile strength between 22 and 27 MPa, an elongation between 40 and 80%, and a shielding effect full-energy peak count of 621.3 s -1 or so.

[0169] Examples 17 to 20

[0170] In Examples 17 to 20, according to the steps of the above-mentioned "2. Preparation method", in step (1), 98.5 parts of maleic anhydride-grafted high-density polyethylene and 0.5 parts of bisphenol A diglycidyl ether are used; in step (4), the process parameters of the disk-shaped solid-phase force chemical reactor are: the grinding pressure is 5 MPa, the temperature of the disk surface is controlled at 15 to 35 °C by introducing circulating cooling liquid, and the circulation grinding is carried out 10 times, and the disk rotation speed is 150 revolutions per minute; in step (5), the process parameters of the reactive extrusion include: the rotation speed is 130 rpm, and the temperature is 190 to 230 °C; finally, composite pellets are prepared, which are high-filled and low-heterogeneity composites introducing the vitrimer micro-crosslinked structure.

[0171] To verify the technical effects of Examples 17 to 20, the composite pellets are prepared into nuclear shielding composite plates by hot pressing as samples. The process parameters of the hot pressing include: the pressure is 15 MPa, the temperature is 200 °C, and the hot pressing times are 20 min, 60 min, 120 min, and 360 min corresponding to Example 17, Example 18, Example 19, and Example 20 in sequence.

[0172] The nuclear shielding composite plates prepared in Examples 17 to 20 have a tensile strength of about 22 to 26 MPa, an elongation between about 80 and 180%, and a shielding effect full-energy peak count of 621.7 s -1 or so.

[0173] Comparative Example 1

[0174] In this comparative example, a comparative sample is prepared by a traditional method, which mainly includes the following steps according to the weight parts:

[0175] (1) Mix the raw materials including the following components evenly as the mixture:

[0176] 30 parts of maleic anhydride-grafted high-density polyethylene,

[0177] 70 parts of silane coupling agent-modified tungsten powder,

[0178] (2) Extrude the mixture obtained in step (1) by a twin-screw extruder to prepare composite pellets;

[0179] Among them, the process parameters of the extrusion by the twin-screw extruder include: the rotation speed is 50 rpm, and the temperature is 190 to 220 °C;

[0180] (3) The composite pellets obtained in step (2) are prepared into a composite board by hot pressing to serve as a comparative sample. The process parameters of the hot pressing include: the pressure is controlled and maintained at 12 MPa, the temperature is 200 °C, and the hot pressing time is 20 min.

[0181] For the prepared composite board, the tensile strength is 26.8 MPa, the elongation at break is 24.2%, and the shielding effect full-energy peak count is 648.8 s. -1 。

[0182] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.

Claims

1. A preparation method of a highly filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure, characterized in that It mainly includes the following steps: (1) By mass parts, mix the raw materials including the following components evenly to obtain mixture A: 92 - 99 parts of maleic anhydride grafted polymer, 0.5 - 3 parts of zinc acetylacetonate monohydrate, 0.5 - 5 parts of liquid crosslinking agent; The total of the maleic anhydride grafted polymer, zinc acetylacetonate monohydrate, and liquid crosslinking agent is 100 parts; Among them, the maleic anhydride grafted polymer is the product obtained by grafting modification of thermoplastic plastics with maleic anhydride, and the liquid crosslinking agent is selected from liquid crosslinking agents with multiple epoxy groups in its chemical structural formula; (2) Use reactive extrusion for the mixture A obtained in step (1) to prepare an intermediate composite pellet with an epoxy - based vitrimer micro - crosslinked structure; Among them, the process parameters of the reactive extrusion include: rotation speed 30 - 150 rpm, temperature 170 - 210 °C; (3) Add silane coupling agent - modified inorganic filler to the intermediate composite pellet obtained in step (2) according to a mass ratio of 3:(6 - 8), and mix evenly to obtain mixture B; (4) Add the mixture B obtained in step (3) into a disk - shaped solid - phase force chemical reactor for grinding and pulverization. After the grinding is completed, collect the composite powder; among them, the process parameters of the disk - shaped solid - phase force chemical reactor are: grinding pressure 3 - 6 MPa, the temperature of the disk surface is controlled at 15 - 35 °C by introducing circulating cooling liquid, circulate and grind 5 - 15 times, and the rotation speed of the disk is 50 - 200 revolutions per minute; (5) Use reactive extrusion for the composite powder obtained in step (4) to prepare a composite pellet, which is a high - filled and low - heterogeneity composite material introducing the vitrimer micro - crosslinked structure; Among them, the process parameters of the reactive extrusion include: rotation speed 30 - 150 rpm, temperature 190 - 230 °C.

2. The preparation method according to claim 1, characterized in that: The maleic anhydride grafted polymer described in step (1) is a maleic anhydride grafted polyolefin polymer.

3. The preparation method according to claim 1, characterized in that: When the maleic anhydride grafted polymer described in step (1) is maleic anhydride grafted high - density polyethylene, its preparation method mainly includes the following steps: By weight parts, mix 97 - 99 parts of high - density polyethylene with 0.1 - 0.5 parts of peroxide initiator and 1 - 3 parts of maleic anhydride evenly, and use reactive extrusion to prepare maleic anhydride grafted high - density polyethylene; Among them, the process parameters of the reactive extrusion include: rotation speed 170 - 200 rpm, temperature 180 - 230 °C.

4. The preparation method according to claim 1, characterized in that: The reactive extrusion described in step (2) is realized by a twin - screw extruder.

5. The preparation method according to claim 1, characterized in that: The liquid crosslinking agent described in step (1) is bisphenol A diglycidyl ether.

6. The high - filled and low - heterogeneity composite material introducing the vitrimer micro - crosslinked structure prepared by the preparation method of the high - filled and low - heterogeneity composite material introducing the vitrimer micro - crosslinked structure as described in claim 1.

7. The application of the high - filled and low - heterogeneity composite material introducing the vitrimer micro - crosslinked structure as described in claim 6 in the preparation of thermoplastic products.

8. A functional composite board made of a highly filled and low-heterogeneity composite material introducing a vitrimer micro-crosslinked structure as described in claim 6, characterized in that it is A functional composite board is prepared by hot pressing a highly filled and low-heterogeneity composite material including a vitrimer micro-crosslinked structure. The process parameters of the hot pressing include: a pressure of 10 to 20 MPa, a temperature of 160 to 230 °C, and a hot pressing time of 10 minutes to 12 hours.

Citation Information

Patent Citations

  • Mechanico-chemical reactor

    CN1130545A

  • An industrial millstone-shaped solid-phase mechanochemical reactor

    CN114534660B